Evaluation of flood determination with various methods: Case study of Ayamama Creek - Orkan Özcan (Doğal Afetler ve Çevre Dergisi)
In many developing countries, rapid urbanization, disaster risks and affectability pose a great problem. Uncontrolled developments will bring out the inherent risks related with high-density environments and inadequate infrastructure. Advances in mapping hazardous areas have created new opportunities for assessing population vulnerabilities, doing designs to withstand against destructive forces and reducing losses. The aim of this study is to evaluate and compare the most used methods including i) Multi Criteria Decision Analysis, ii) Hydraulic Modeling, iii) Information Diffusion Theory and iv) SCS-CN (Soil Conservation Service Curve Number) in flood analysis. In the light of the results; 1995 buildings were found to be in vulnerable zones in total and 420 of them were found to be in a very high vulnerable zones according to the prepared affectability map. Hydrologic modeling results based on the defined discharge rate showed that 73 hectares of the urbanized area will be affected in the event of 185m3/s of steady flow in Ayamama Creek and these areas were determined in GIS. Based upon the nearest neighbour object-based classification, total of 1859 buildings were defined to be affected by a potential flood. Curve numbers of the catchment were determined by using SCS-CN method and used in Information Diffusion method. According to the results of this method, when the Ayamama Creek reaches 180m3/s of flow rate, the probability of flood occurrence is estimated to be %97.2 and it was determined that the flood waters will be effective in about 50 hectares of the area.